Kualitas Pelayanan Kesehatan Rumah Sakit Buluye Napoa’e Moutong Di Desa Salumpengut Kecamatan Moutong Kabupaten Parigi Moutong - Zikra, Mohamad; Nuraisyah; Firmansyah, Andi Maman (JPS: Journal of Publicness Studies, 2025)
The purpose of this study was to determine the Quality of Health Services at Buluye Napoa'e Moutong Hospital, Parigi Moutong Regency. This study used a qualitative descriptive method. Informants in this study numbered 7 people, and the determination of research informants used a purposive sampling technique. The types of data used were primary and secondary data. Data collection techniques used observation, interviews, documentation, and triangulation techniques. Based on the results of the study, it was concluded that the Quality of Health Services at Buluye Napoa'e Moutong Hospital, Parigi Moutong Regency, seen from the aspect of physical evidence (tangibles), there are still several deficiencies in the waiting room facilities and lighting that need improvement. Then from the aspect of reliability, it shows that the hospital has a reliable work system in providing medical services to patients. Then, seen from the aspect of responsiveness, it is not running optimally. This is caused by hospital employees who are still unable to complete the tasks of health services needed by the community. In addition, public service from the aspect of assurance shows that medical personnel are able to build a sense of security and patient trust through clear communication, courtesy, and good professional competence. Lastly, from the aspect of attention (empathy), it has been going well, because health workers show personal attention to patients, such as greeting them, asking about their condition, and providing emotional support.